TECHNICAL-ECONOMIC EVALUATION ASSOCIATED WITH THE TECHNOLOGICAL IMPROVEMENT OF THE PANELA PLANT AT THE UEB DERIVATIVES CHIQUITICO FABREGAT - Suárez Bolaños, Ernesto; Pérez Navarro, Omar; Suárez Pargas, Claudia M. (Centro Azúcar Journal, 2025)
Introduction: The production of panela, at the Chiquitico Fabregat company, is a potentially sustainable and feasible alternative if more favorable technological conditions than those currently existing can be implemented. Objective: To evaluate technically and economically the panela production of the Chiquitico Fabregat company considering the currently installed technology and an improved technological proposal. Materials and Methods: The technological and operational evaluation of the installed technology was carried out, determining its main weak points and proposing technological improvements that allow increasing efficiency, quality and reducing the energy impacts of the process. Technological schemes were prepared and the mass and energy balances were developed for both proposals, determining the material and energy demands. Based on the technological and operational evaluation and the information related to the acquisition of the equipment, a comparative analysis of the technical-economic behavior was carried out with dynamic indicators for both scenarios. Results and Discussion: The stages of reception, grinding, evaporation and manufacturing of panela were perfected. In evaporation, the kettles at atmospheric pressure were replaced by vacuum pans. The improved proposal increased energy efficiency and productivity, including granulated panela as a new product, and achieved more favorable dynamic economic indicators than current technology. Conclusions: The proposed technological modifications guarantee the sustainability of panela production, delivering a stable quality product, increasing added value and market acceptance and achieving more favorable economic-financial results.